THE CONCEPT, ESSENCE OF THE RIGHTS OF THE CHILD AND THE BASICS OF THEIR LEGAL PROTECTION (TAMADDUN NURI JURNALI, 2025)
This article explores the concept of children's rights, their essence, and the foundations of their legal protection. It analyzes the fundamental rights and freedoms of children based on international and national legal documents, discusses mechanisms for their protection, as well as existing challenges and possible solutions.